Effects of reproductive experience on cost-benefit decision making in female rats - Faraji, Mojdeh; Viera-Resto, Omar A.; Setlow, Barry; Bizon, Jennifer L. (Frontiers in Behavioral Neuroscience, 2024)
Many individuals undergo mating and/or other aspects of reproductive experience at some point in their lives, and pregnancy and childbirth in particular are associated with alterations in the prevalence of several psychiatric disorders. Research in rodents shows that maternal experience affects spatial learning and other aspects of hippocampal function. In contrast, there has been little work in animal models concerning how reproductive experience affects cost-benefit decision making, despite the relevance of this aspect of cognition for psychiatric disorders. To begin to address this issue, reproductively experienced (RE) and reproductively naïve (RN) female Long-Evans rats were tested across multiple tasks that assess different forms of cost-benefit decision making. In a risky decision-making task, in which rats chose between a small, safe food reward and a large food reward accompanied by variable probabilities of punishment, RE females chose the large risky reward significantly more frequently than RN females (greater risk taking).In an intertemporal choice task, in which rats chose between a small, immediate food reward and a large food reward delivered after a variable delay period, RE females chose the large reward less frequently than RN females. Together, these results show distinct effects of reproductive experience on different forms of cost-benefit decision making in female rats, and highlight reproductive status as a variable that could influence aspects of cognition relevant for psychiatric disorders.